Optogenetic Manipulations of Amygdala Neurons Modulate Spinal Nociceptive Processing and Behavior Under Normal Conditions and in an Arthritis Pain Model - Mazzitelli, Mariacristina; Marshall, Kendall; Pham, Andrew; Ji, Guangchen; Neugebauer, Volker (Frontiers in Pharmacology, 2021)
The amygdala is an important neural substrate for the emotional–affective dimension of pain and modulation of pain. The central nucleus (CeA) serves major amygdala output functions and receives nociceptive and affected–related information from the spino-parabrachial and lateral–basolateral amygdala (LA–BLA) networks. The CeA is a major site of extra–hypothalamic expression of corticotropin releasing factor (CRF), and amygdala CRF neurons form widespread projections to target regions involved in behavioral and descending pain modulation. Here we explored the effects of modulating amygdala neurons on nociceptive processing in the spinal cord and on pain-like behaviors, using optogenetic activation or silencing of BLA to CeA projections and CeA–CRF neurons under normal conditions and in an acute pain model. Extracellular single unit recordings were made from spinal dorsal horn wide dynamic range (WDR) neurons, which respond more strongly to noxious than innocuous mechanical stimuli, in normal and arthritic adult rats (5–6 h postinduction of a kaolin/carrageenan–monoarthritis in the left knee). For optogenetic activation or silencing of CRF neurons, a Cre–inducible viral vector (DIO–AAV) encoding channelrhodopsin 2 (ChR2) or enhanced Natronomonas pharaonis halorhodopsin (eNpHR3.0) was injected stereotaxically into the right CeA of transgenic Crh–Cre rats. For optogenetic activation or silencing of BLA axon terminals in the CeA, a viral vector (AAV) encoding ChR2 or eNpHR3.0 under the control of the CaMKII promoter was injected stereotaxically into the right BLA of Sprague–Dawley rats. For wireless optical stimulation of ChR2 or eNpHR3.0 expressing CeA–CRF neurons or BLA–CeA axon terminals, an LED optic fiber was stereotaxically implanted into the right CeA. Optical activation of CeA–CRF neurons or of BLA axon terminals in the CeA increased the evoked responses of spinal WDR neurons and induced pain-like behaviors (hypersensitivity and vocalizations) under normal condition. Conversely, optical silencing of CeA–CRF neurons or of BLA axon terminals in the CeA decreased the evoked responses of spinal WDR neurons and vocalizations, but not hypersensitivity, in the arthritis pain model. These findings suggest that the amygdala can drive the activity of spinal cord neurons and pain-like behaviors under normal conditions and in a pain model.